A way with words - Redman, Stuart (Cambridge Univ. Press, 1996)
A photocopiable resource book of vocabulary activities. This resource book of vocabulary practice activities enables teachers to teach vocabulary communicatively in the classroom. The book provides a variety of stimulating activities which require learners to actively use the target vocabulary. It develops learning skills, helping learners to become more efficient in organising, storing and remembering new vocabulary. It is easy to use with clear teacher's notes on the left hand pages and facing photocopiable worksheets on the right. This lower-intermediate to intermediate resource book is accompanied by a cassette for further practice of the key vocabulary